2014
DOI: 10.4037/ccn2014731
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurse Work Environments 2013: A Status Report

Abstract: 1 Developed by an expert panel, these standards were based on published and experiential evidence from nurses and other health care experts throughout the United States. More than 50 content experts, representing a wide range of roles, acute and critical care settings, and geographic locations, reviewed the standards, critical elements, and explanatory text to establish face validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 41 publications
3
91
1
5
Order By: Relevance
“…First, given the simulation-based study design, external validity may be questioned. Nevertheless, hospital-based research on incivility and its consequences 19,[40][41][42][43] suggests that our findings are consistent with the "real world" and, if anything, underestimate the magnitude of effects. Moreover, simulations are becoming more widespread in medicine as an investigative tool.…”
Section: Figuresupporting
confidence: 70%
“…First, given the simulation-based study design, external validity may be questioned. Nevertheless, hospital-based research on incivility and its consequences 19,[40][41][42][43] suggests that our findings are consistent with the "real world" and, if anything, underestimate the magnitude of effects. Moreover, simulations are becoming more widespread in medicine as an investigative tool.…”
Section: Figuresupporting
confidence: 70%
“…The nurses in this study stated that to improve patient experiences, the nurses should have autonomy over their own practice; the quality of patient care is greater when the foundations for quality of care are present in their present job. In the USA, the nurses demonstrated that the accessibility of educational chances was related to nurses' perceptions of the quality of care (Ulrich et al, 2006). Kelly, Kutney-Lee, Lake, and Aiken, 2013 reported that the nurses rate highest score in foundations for quality of care compare to other categories.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9,11,13,14,21,22] In one study, the participation in shared governance enhanced the leadership skills of participants, but this was accompanied with many barriers. [8] Two studies revealed improvement in the communication and collaboration among nurses who utilized SGM.…”
Section: Introductionmentioning
confidence: 99%